The drop-jump screening test. Difference in lower limb control by gender and effect of neuromuscular training in female athletes - Noyes, F. R.; Barber-Westin, S. D.; Fleckenstein, C.; Walsh, C.; West, J. (The American Journal of Sports Medicine, 2005)
Background: A valgus lower limb alignment has been noted during noncontact anterior cruciate ligament injuries. A video drop-jump test can indicate an athlete`s ability to control lower limb axial alignment in the coronal plane.